The beast of Soggy Moo - Howard , Martin (London Walker Entertainment, 2015)
Characters from the CBBC and Aardman series Shaun the Sheep step from screen to page in the 2nd book in illustrated fiction series Tales from Mossy Bottom Farm
Keywords: Farm animals Fiction(3Rs; First chapter Fiction